2023
DOI: 10.20945/2359-3997000000537
|View full text |Cite
|
Sign up to set email alerts
|

Predictive factors and risk analysis of recurrent laryngeal nerve invasion in papillary thyroid carcinoma ≤ 1 cm

Abstract: Objective:The recurrent laryngeal nerve (RLN) may be involved by papillary thyroid carcinoma ≤ 1 centimeter (PTC ≤ 1 cm). Current study investigated the predictive factors of RLN invasion in PTC ≤ 1 cm, the risk factors of disease recurrence in RLN invaded cases and the results of surgical management for RLN invasion. Materials and methods: Data of 374 PTC ≤ 1 cm patients were retrospectively collected. We performed univariate and multivariate analysis to identify predictive factors of RLN invasion and risk fa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 47 publications
0
2
0
Order By: Relevance
“…Our study concluded that radical surgical treatment is an important influence on the prognosis of LATC, and long-term clinical practice and the results of a large number of case summaries have also proved that the choice of the first standardized surgical approach determines the final outcome of TC, and is the most important factor determining the prognosis and efficacy of treatment. However, studies have shown that despite initial standardized treatment, recurrence or DM still occurs in about 15 % of TC patients [ 30 ]. LATC can significantly invade the surrounding vital structures and has a poorer prognosis, and its surgical scope is extensive and involves the resection and reconstruction of vital organs, with greater surgical trauma and surgical risk and a higher complication rate, so discussions on the appropriate extent of surgical resection for LATC remain controversial [ 31 ].…”
Section: Discussionmentioning
confidence: 99%
“…Our study concluded that radical surgical treatment is an important influence on the prognosis of LATC, and long-term clinical practice and the results of a large number of case summaries have also proved that the choice of the first standardized surgical approach determines the final outcome of TC, and is the most important factor determining the prognosis and efficacy of treatment. However, studies have shown that despite initial standardized treatment, recurrence or DM still occurs in about 15 % of TC patients [ 30 ]. LATC can significantly invade the surrounding vital structures and has a poorer prognosis, and its surgical scope is extensive and involves the resection and reconstruction of vital organs, with greater surgical trauma and surgical risk and a higher complication rate, so discussions on the appropriate extent of surgical resection for LATC remain controversial [ 31 ].…”
Section: Discussionmentioning
confidence: 99%
“…Falk et al demonstrated that complete excision of PTC with resection of the RLN did not improve survival compared to incomplete excision [ 39 ]. In the study of Yang et al, tumor shaving showed superiority in preserving RLN function without increasing the risk of recurrence in patients with papillary thyroid microcarcinoma [ 40 ]. The RLN invasion was commonly associated with other invaded structures.…”
Section: Discussionmentioning
confidence: 99%